Acquired resistance during adoptive cell therapy by transcriptional silencing of immunogenic antigens. (3rd August 2019) - Wylie, Ben; Chee, Jonathan; Forbes, Catherine A; Booth, Mitchell; Stone, Shane R; Buzzai, Anthony; Abad, Ana; Foley, Bree; Cruickshank, Mark N; Waithman, Jason
ABSTRACT: Immunotherapies such as adoptive cell therapy (ACT) are promising treatments for solid cancers. However, relapsing disease remains a problem and the molecular mechanisms underlying resistance are poorly defined. We postulated that the deregulated epigenetic landscape in cancer cells could underpin the acquisition of resistance to immunotherapy. To address this question, two preclinical models of ACT were employed to study transcriptional and epigenetic regulatory processes within ACT-treated cancer cells. In these models ACT consistently causes robust tumor regression, but resistance develops and tumors relapse. We identified down-regulated expression of immunogenic antigens at the mRNA level correlated with escape from immune control. To determine whether this down-regulation was under epigenetic control, we treated escaped tumor cells with DNA demethylating agents, azacytidine (AZA) and decitabine (DEC). AZA or DEC treatment restored antigen expression in a proportion of the tumor population. To explore the importance of other epigenetic modifications we isolated tumor cells refractory to DNA demethylation and screened clones against a panel of 19 different epigenetic modifying agents (EMAs). The library of EMAs included inhibitors of a range of chromosomal and transcription regulatory protein complexes, however, when tested as single agents none restored further antigen expression. These findings suggest that tumor cells employ multiple epigenetic and genetic mechanisms to evade immune control, and a combinatorial approach employing several EMAs targeting transcription and genome stability may be required to overcome tumor resistance to immunotherapy.